2017
DOI: 10.1016/j.triboint.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Nano-indentation mapping of fretting-induced surface layers

Abstract: Tribologically modified surface layer results from the energy dissipated in the frictional contact area. This layer usually has a different elastic modulus and hardness from the substrate, and its structure corresponds to the intermediate stage between a material of the first-body and debris of the third-body. Even though, the existence of the tribologically transformed structure in the fretting contact has been well proven, the formation and mechanical transformation mechanisms are still not clear. Hence, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Fretting wear was carried out using fretting device with a dedicated electrodynamic shaker as reported in [30][31][32]. All experiments were conducted in dry conditions at 5Hz frequency and ±100 m displacement amplitude.…”
Section: Tribological Testingmentioning
confidence: 99%
“…Fretting wear was carried out using fretting device with a dedicated electrodynamic shaker as reported in [30][31][32]. All experiments were conducted in dry conditions at 5Hz frequency and ±100 m displacement amplitude.…”
Section: Tribological Testingmentioning
confidence: 99%
“…It was found that the TTS nucleated relatively quickly, and after 100 cycles a TTS layer of 100 µm thickness was observed. In order to analyse the evolution of the TTS layer quantitatively, the dissipated energy approach and fretting maps method were proposed [24,25]. It was also found that the increase of hardness during fretting can be related to the strain-hardening in metals [25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyse the evolution of the TTS layer quantitatively, the dissipated energy approach and fretting maps method were proposed [24,25]. It was also found that the increase of hardness during fretting can be related to the strain-hardening in metals [25]. Strain-hardening occurs during plastic deformation, which is induced by the dislocation and twinning of metal crystals [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Fretting is a small amplitude oscillatory motion wear process between two bodies leading to progressive surface damage by inducting sub-surface material transformations [18].…”
Section: Introductionmentioning
confidence: 99%